Life changes during childhood - Hurme, Helena (1981)
The study concerns the instability of the child's environment. Methodologically, it represents the life event research tradition. The theoretical framework combines features of stress theory, McReynold's theory on the impact of cognitive incongruence and Pulkkinen's theory concerning self-control in children. The study consisted of four parts, which cover the most central phases of life event research. Study A consisted of ratings made by 70 Finnish child guidance workers on the readjustment required at four age levels by 30 life events. The results showed that the death of the mother was rated as the most serious event at all age levels. There were considerable differences between the ratings for the different age groups. The re-test reliability was very high, about .85. There was a remarkably high correspondence with data obtained in other countries, especially when the wording of the events was identical. Study B concerned the occurrence of both single life events and indexes of abundant change. Study C concerned their impact. In study C, data were gathered using the thematic interview, a semi-structured method, partly developed by the author for this study. The results showed that children who had experienced much change showed weak self-control and many behavioural problems. Study D analyzed the maternal factors affecting this relationship. A lack of planfulness and initiative in the mother as well as her anomia were connected with the child's weak self-control, especially in the high change group.